UV treatment for degradation of chemical contaminants in food: A review. Issue 2 (23rd January 2021) - He, Jiang; Evans, Natasha Marie; Liu, Huaizhi; Zhu, Yan; Zhou, Ting; Shao, Suqin
Abstract: Application of ultraviolet (UV) irradiation for the degradation of chemical contaminants in food products has gained more and more interest in the past two decades. The majority of the research in this field was on mycotoxins, especially aflatoxins and patulin, with limited studies on pesticide residues and other chemical contaminants in food. These studies have been focused on identifying the structure and toxicity of degradation products, investigating the influence of UV treatment factors on the degradation efficiency, determining the impact of UV treatment on the quality of food products, and developing updated UV treatment methods such as TiO2 induced photocatalytic degradation. The summary of published literatures provided insights into future research opportunities in this area, which include determining a standard for the UV treatment description, working with naturally contaminated samples rather than artificially spiked samples, conducting pilot plant or industrial scale studies, examining more targets and conducting multi‐targets studies, and developing more innovative methods for UV treatment.